PROSES PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PENGEMBANGAN USAHA MINA PEDESAAN (Studi Deskriptif Di Desa Karang Dayu Kecamatan Baureno Kabupaten Bojonegoro) - Rina Afifatul Khumairoh; Sri Wahyuni; Agus Wahyudi (Faculty of Social and Political Science, 2019)
Poverty almost happens in all regions. Applying community empowerment is one of the solutions to increase the economy. As an alteration, the region will be a sample for people to change the economy and a new industry will be established. People of Karang Dayu Village is an agrarian that have problem of flood and they work as fishery processors and marketers. To resolve economy problems which happened at POHLAKSAR in Karang Dayu Village in 2009, Minister of Maritime Affairs and Fisheries had launched National Maritime Affairs and Fisheries of Independent community Empowerment program (PNPM-MKP). The purpose of this research is to describe and analyze how to apply social economy of community program and the alteration of social community caused by Direct Community Assistance (BLM) Development of Rural Mina Business (PUMP) Fishery Program. This research uses descriptive quality method which referring to how the procces of applying the program and how the alteration of POKLAHSAR social community. Data collection technique uses primary data through interview. and secondary data from online media that discuss about community empowerment. The result shows the social alteration in community who receives the support from BLM PUMP Fishery Program that have positive or negative economy influences.